Соціально-політичне значення культивування опійного маку в Афганістані - Святуха, І.А.; Sviatukha, I. (Харківський національний університет імені В.Н. Каразіна, 2013)
Розглядаються основні передумови і фактори, а також історичний розвиток нарковиробництва в Афганістані. Відзначається вплив руху Талібан на динаміку макових посівів та обсягів виробництва опію в країні. Досліджується економічний ефект від виробництва опію для населення, оцінюються масштаби залучення населення Афганістану у процесі виробництва опію. Доводиться, що культивування опійного маку стало стратегією виживання для афганських селян за умов відсутності еквівалентної за рівнем доходів альтернативи. A look at the main causes and factors, as well as the historical dynamics of drug production evolution in Afghanistan. The Talihban movement’s influence on mass poppy cultivation and production is shown. The research focuses on the economic effects of poppy production for the population, as well as the amount of local citizens taking part in the production process. It is proved that poppy cultivation has become a necessary survival strategy for afghan lower-class due to lack of similar paying labour within the country.
The social and political effects of poppy cultivation in Afghanistan
Keywords: опійний мак; опіати; Талібан; наркобізнес; Афганістан; Poppy; Opiates; Talihban; drug industry; Afghanistan